Occult Talaromyces marneffei Infection Unveiled by the Novel Mp1p Antigen Detection Assay. (19th October 2020) - Ly, Vo Trieu; Thanh, Nguyen Tat; Thu, Nguyen Thi Mai; Chan, Jasper; Day, Jeremy N; Perfect, John; Nga, Cao Ngoc; Vinh Chau, Nguyen Van; Le, Thuy
Abstract: Talaromyces marneffei causes fatal invasive mycosis in Southeast Asia. Diagnosis by culture has limited sensitivity and can result in treatment delay. We describe the use of a novel Mp1p enzyme immunoassay (EIA) to identify blood culture–negative talaromycosis, subsequently confirmed by bone marrow cultures. This EIA has the potential to speed diagnosis, enabling early therapy initiation.